Micromamíferos del Mioceno superior y Plioceno de la Cuenca de Calatayud (centro de España) - Sanz Rubio, Enrique; Van Dam, Jan (Coloquios de Paleontología, 2003)
A new series of late Neogene small mammal samples from the Calatayud Basin (Central Spain) is described. The samples were collected from the central part of the basin at Cortasogas and Maluenda under the supervision of Remmert Daams and Manuel Hoyos in the early eighties and more recently in 1998. On the basis of small mammal teeth, the age of Cortasogas 1 and 2 is estimated at 8.5-7.5 and 9.5-8.5 Ma, respectively. The age of Maluenda 1A and 1B is estimated at 11-9 and 5-4 Ma, respectively. These results provide new constraints on the age and nature of the regionally important sedimentary discontinuity between the Intermediate and Upper units in the basin. They indicate that in these areas, where sediments from the Intermediate unit and the basal red siliciclastic subunit of the Upper unit have their minimum thickness, a major part of the Upper Miocene is missing. The youngest locality Maluenda 3 has an age of 4.5- 3 Ma, providing additional evidence for a Pliocene age of the upper carbonatic fluviolacustrine subunit of the Upper sedimentary unit.